Penyuluhan Hukum Penanggulangan Kekerasan Seksual di Desa Anjani, Lombok Timur - suheflihusnaini ashady; Muaidy Yasin; Wahyunadi; Aryadi Almau Dudy; Lalu Edy Herman Mulyono; Zahratul Ain Taufik (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
According to a report from the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia, sexual violence in East Lombok Regency, the area of service, is the highest in West Nusa Tenggara Province. This figure, in crime statistics, represents a dark number of crimes, not the actual number. The low number of reported cases is influenced, in part, by limited public knowledge regarding the forms, risk factors, and reporting mechanisms for sexual violence. Following the service, communities in the partner areas experienced increased literacy regarding the forms of sexual violence regulated by various Indonesian laws, enabling them to participate in future efforts to address sexual violence.